Urban intensification of convective rainfall over the Singapore – Johor Bahru region. (25th August 2021) - Simón‐Moral, Andres; Dipankar, Anurag; Doan, Quang‐Van; Sanchez, Claudio; Roth, Matthias; Becker, Erik; Huang, Xiang‐Yu
Abstract: Simulations of five November months (2010–2014) using the urban version of the numerical weather prediction system of the Meteorological Service Singapore (uSINGV) are used to analyse the urban effect on convective precipitation over Singapore and Johor Bahru (Malaysia). The model is able to closely predict locations where rainfall peaks occur, but rainfall totals are overestimated compared to radar data. The temporal variability of rainfall in the region shows that urban areas increase the frequency and severity of rainfall events and that such impact increases with the rainfall intensity. Results show that low‐level moisture advection is enhanced in this coastal conurbation as a result of the strengthening of wind convergence. The latter is likely caused by increasing sea‐breeze strength due to lower surface pressure over the urban area, and higher urban surface roughness, respectively. As a consequence, more precipitable water is available in the region, enhancing convection and increasing the probability of heavy rainfall over the centre and north of Singapore island and Johor Bahru. Stronger convection further increases moisture advection from the vicinity. By studying the temporal variability and the spatial distribution of rainfall events, the present study provides new insights on the urban impact on heavy rainfall in tropical areas. The conclusions are only valid for the November inter‐monsoon period, when local forcing, rather than large‐scale influences, dominates rainfall generation. Abstract : Singapore and its neighbouring city Johor Bahru, Malaysia, increase the frequency and intensity of rainfall events during the November inter‐monsoon period and this intensification increases with the intensity of the event. Based on model simulations, the combination of the two cities is found to strengthen low‐level sea‐breeze moisture advection, leading to enhanced convection and increased rainfall totals over the urban area. Stronger convection over the city further reinforces horizontal moisture flux from the vicinity.